Interaction Effects of 3-Mercaptohexan-1-ol (3MH), Linalool and Ethyl Hexanoate on the Aromatic Profile of South African Dry Chenin Blanc Wine by Descriptive Analysis (DA) - Wilson, C.; Brand, J.; du Toit, W.; Buica, A. (South African Journal of Enology and Viticulture, 2018)
Interaction studies are some of the most interesting sensory experiments that highlight the effect of composition on wine perception. The use of single compounds, viz. an ester (ethyl hexanoate), a terpene (linalool) and a thiol (3-mercaptohexanol, 3MH), which have previously been shown to be representative of Chenin Blanc wines, resulted in typical descriptors for these compounds, such as ‘apple, ‘floral’ and ‘guava’ respectively. Interaction effects were observed between the compounds, and these were reflected in both the nature and the level of attributes generated. Additionally, interaction effects between the compounds (singles and combinations) and the wine matrix indicated that the latter plays an important role in the perception of wine aromas. The use of a dearomatised neutral wine base added an extra dimension to this study, which usually is done in a simpler matrix, such as a model wine.